Effect of herbicidal weed management on wheat (Triticum aestivum) productivity and weed growth - Tiwari, S N; Tewari, A N; Tripathy, A K (The Indian Journal of Agricultural Sciences, 2005)
An experiment was carried out during the winters of 1998-2000 to judge the efficacy of new herbicides and their tank mixtures in controlling associated weed species in irrigated dwarf wheat (Triticum aestivum L. emend. Fiori & Paol.). Isoproturon (750 g/ha) + 2,4-D sodium salt (500 g/ha) eliminated weed competition (WCE 88.16%) resulting in increased mean seed yield (4.58 tonnes/ha) closely followed by isoproturon (750 g/ha) + metsulfuron methyl (3 g/ha). Metsulfuron methyl (3 g/ha) proved to be good alternative of 2,4-D sodium salt (500 g/ha) with regard to broad-leaved weed control. Metribuzin showed efficient control of grassy as well as broad-leaved weeds but depressed grain yield.